A systematic review of studies on connected speech processing: Trends, key findings, and implications - Bi, Huichao; Zare, Samad; Kania, Ursula; Yan, Rong (Frontiers in Psychology, 2022)
Connected speech processing (CSP) is of great significance to individuals’ language and cognitive development. It is particularly crucial not only for clinical detection and treatment of developmental disorders, but also for the foreign/second language teaching instructions. However, given the importance of this field, there is a clear lack of systematic reviews that summarize the key findings of previous studies. To this end, through searching in the scientific databases PsycInfo, Scopus, PubMed, ERIC, Taylor and Francis, and Web of Science, the present study identified 128 core CSP articles with high reference values according to PRISMA guidance and the following results were obtained through quantitative analysis and qualitative comparative synthesis: (1) The number of studies on CSP published per year showed an upward trend; however, most focused on English language, whereas the studies on other languages were comparatively rare; (2) CSP was found to be affected by multiple factors, among which speech speed, semantics, word frequency and phonological awareness were most frequently investigated; (3) The deficit in CSP capacity was widely recognized as a significant predictor and indicator of developmental disorders; (4) More studies were carried out on connected speech production than on perception; and (5) Almost no longitudinal studies have ever been conducted among either native or non-native speakers. Therefore, future research is needed to explore the developmental trajectory of CSP skills of typically developing language learners and speakers with cognitive disorders over different periods of time. It is also necessary to deepen the understanding of the processing mechanism beyond their performance and the role played by phonological awareness and lexical representations in connected speech processing.